Variants of IL6, IL10, FCN2, RNASE3, IL12B and IL17B loci are associated with Schistosoma mansoni worm burden in the Albert Nile region of Uganda - Nyangiri, Oscar Asanya; Mulindwa, Julius; Namulondo, Joyce; Kitibwa, Anna; Nassuuna, Jacent; Elliott, Alison; Kimuda, Magambo Phillip; Boobo, Alex; Nerima, Barbara; Adriko, Moses; Dunton, Nathan J.; Madhan, Gaganjit Kaur; et al. (PLOS Neglected Tropical Diseases, 2023)
Author summary This study investigated genetic risk factors for high worm burden in a cohort of 606 children aged 10–15 years old in the Albert Nile region of Uganda. Genotyping was conducted on 326 children who comprised the top and bottom 25% of worm burden. Results showed single nucleotide polymorphisms (SNPs) associated with worm burden in the IL6, IL21 and IL17B genes, and a haplotype in the IL10 locus associated with lower worm burden. Expression quantitative trait locus (eQTL) analysis revealed significant gene and worm burden associations in the IL6 region, and expression associations in the IL5, IL21, IL25 and IFNG loci. These findings suggest that immune balance, pathogen recognition and Th17 pathways may be involved in modulating Schistosoma worm burden and that individuals carrying risk variants may be prioritized to improve control efforts.